Factors that influence poor drug compliance among psychiatric clients after discharge at Zomba mental hospital - Kubwalo, G. Ellah (Kamuzu University of Health Sciences, 2022)
This study was conducted to explore factors that influence poor drug compliance among psychiatric clients after discharge at Zomba Mental Hospital. Specifically the study objectives were: to assess knowledge of psychiatric clients on their condition, assess knowledge of psychiatric clients on the importance of drug they receive, assess the attitude and practice of psychiatric clients towards the psychiatric drugs, identify problems/challenges that clients face after discharge and to identify factors that would promote drug compliance at home. The study was conducted at Zomba Mental Hospital and psychiatric clinics of Domasi, Nasawa and Magomero. A quantitative research design was used and 40 psychiatric clients with history of poor drug compliance were selected using convenience sampling. Data was collected through a structured questionnaire. Data was analyzed using Statistical Package for Social Science version 1 1.0. The study has revealed that psychiatric clients have knowledge on psychiatric condition and on the importance of the psychiatric drugs. Despite having IQ knowledge on the importance of the drugs, most of the psychiatric clients have no knowledge on the side effects of the drugs. The study has also indicated that some of psychiatric clients do not comply with drugs because of drowsiness and forgetfulness. Further more the study has revealed that psychiatric clients still face stigma in communities. Basing on the findings, this study recommends that there is a need for Ministry of Health to disseminate information through Information, Education and Communication on side effects of the drugs and their management.